ICT Self-Efficacy, Organizational Support, Attitudes, and the Use of Blended Learning: An Exploratory Study Based on English Teachers in Basic Education - Ye, Long; Kuang, Manteng; Liu, Song (Frontiers in Psychology, 2022)
The study aims to build a model that predicts the behavior of the use of blended learning by English teachers of basic education in China in the environment of repeated lockdowns during the COVID-19 pandemic. It examines the relationships between ICT self-efficacy, the organizational support for blended learning, attitudes toward blended learning and the use of blended learning. Data were collected from 562 teachers using a survey questionnaire. Employing partial least squares structural equation modeling (PLS-SEM), a hypothesized model was tested for path coefficients and predictive power. This study found that ICT self-efficacy and organizational support for blended learning are sound predictors of teachers’ use of blended learning and that the former appeared to be a stronger determinant. In addition, attitudes toward blended learning can directly influence teachers’ use of blended learning and mediate the relationship between ICT efficacy and the use of blended learning and between organizational support for blended learning and the use of blended learning. These three variables account for 54.7% of the variance in teachers’ use of blended learning.